Political Beliefs: A Philosophical Introduction - Traldi, Oliver (Routledge, 2024)
Anyone who’s had an argument about politics with a friend may walk away wondering how this friend could possibly hold the beliefs they do. A few self-reflective people might even wonder about their own political beliefs after such an argument. This book is about the reasons that people have, and could have, for political beliefs: the evidence they might draw on, the psychological sources of their views, and the question of how we ought to form our political beliefs if we want to be rational. The book’s twenty-four chapters are divided into four larger parts, which cover the following: (1) the differences between political and other types of beliefs, (2) theories of political belief formation, (3) sources of our political beliefs and how we might evaluate them, and (4) contemporary phenomena – like polarization, fake news, and conspiracy theories – related to political beliefs. Along the way, the book addresses questions that will arise naturally for many readers, like: Does the news you choose to watch and your own social media leave you stuck in an “information bubble”? Are you committed to a certain ideology because of the history of your society? Are people who believe “fake news“ always acting irrationally? Does democracy do a good job of figuring out what’s true? Are some political beliefs good and some evil? As the book investigates these and other questions, it delves into technical, philosophical topics like epistemic normativity, the connection between belief and action, pragmatic encroachment, debunking arguments, and ideology critique. Chapter summaries and discussion questions will help students and all interested readers better grasp this new, important area on the border of politics and philosophy. Key Features Systematically covers the political turn in contemporary epistemology and integrates it with important work in other fields (like psychology and political science) In addition to deep coverage of the nature of political belief, includes material on the ethics of political belief and how we ought to form our beliefs Approaches topics that naturally interest students like political disagreement, fake news, conspiracy theories, and the morality of belief Provides a Conclusion and Discussion Questions at the end of each chapter, prompting student readers to think more clearly and deeply about the material they’ve read The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 International license.